Point-of-care blood coagulation assay enabled by printed circuit board-based digital microfluidics. Issue 4 (20th January 2022) - Li, Donghao; Liu, Xinyu; Chai, Yujuan; Shan, Jieying; Xie, Yihan; Liang, Yong; Huang, Susu; Zheng, Weidong; Li, Zida
Abstract : Using printed circuit board-based digital microfluidics, a point-of-care blood coagulation assay was developed to simultaneously assess the clotting tendency and the stiffness of the resultant blood clot. Abstract : The monitoring of coagulation function has great implications in many clinical settings. However, existing coagulation assays are simplex, sample-consuming, and slow in turnaround, making them less suitable for point-of-care testing. In this work, we developed a novel blood coagulation assay that simultaneously assesses both the tendency of clotting and the stiffness of the resultant clot using printed circuit board (PCB)-based digital microfluidics. A drop of blood was actuated to move back and forth on the PCB electrode array, until the motion winded down as the blood coagulated and became thicker. The velocity tracing and the deformation of the clot were calculated via image analysis to reflect the coagulation progression and the clot stiffness, respectively. We investigated the effect of different hardware and biochemical settings on the assay results. To validate the assay, we performed assays on blood samples with hypo- and hyper-coagulability, and the results confirmed the assay's capability in distinguishing different blood samples. We then examined the correlation between the measured metrics in our assays and standard coagulation assays, namely prothrombin time and fibrinogen level, and the high correlation supported the clinical relevance of our assay. We envision that this method would serve as a powerful point-of-care coagulation testing method.